Integrated marketing communications, strategies, and tactical operations in sports organizations - Alonso Dos Santos, Manuel, 1981- (IGI Global, 2019)
"This book disseminates the latest trends in strategy and tactics carried out in sports organizations through a compendium of research and case studies in the sports industry"--